2019
DOI: 10.1016/j.joca.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy-based water content is a negative predictor of articular human cartilage mechanical function

Abstract: s u m m a r yObjective: Probing the change in water content is an emerging approach to assess early diagnosis of osteoarthritis (OA). We herein developed a new method to assess hydration status of cartilage nondestructively using Raman spectroscopy (RS), and showed association of Raman-based water and organic content measurement with mechanical properties of cartilage. We further compared Raman-based water measurement to gravimetric and magnetic resonance imaging (MRI)-based water measurement. Design: Eighteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…There has been growing interest in Raman spectroscopy as a potential OA diagnostic technology, building upon prior work on IR spectroscopy [30][31][32] . Prior ex vivo studies have examined Raman spectral changes in explanted late stage OA cartilage tissues [20][21][22]33 or cartilage subjected to mechanical damage [16][17][18] . With the exception of Unal et al 33 , who used highwavenumber Raman peak ratios to measure cartilage water content but not GAG or collagen, prior Raman assessments have consisted of univariate peak analysis or principle component analysis (PCA), which do not provide quantification of biochemical or structural tissue changes relevant to the tissue's functional performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been growing interest in Raman spectroscopy as a potential OA diagnostic technology, building upon prior work on IR spectroscopy [30][31][32] . Prior ex vivo studies have examined Raman spectral changes in explanted late stage OA cartilage tissues [20][21][22]33 or cartilage subjected to mechanical damage [16][17][18] . With the exception of Unal et al 33 , who used highwavenumber Raman peak ratios to measure cartilage water content but not GAG or collagen, prior Raman assessments have consisted of univariate peak analysis or principle component analysis (PCA), which do not provide quantification of biochemical or structural tissue changes relevant to the tissue's functional performance.…”
Section: Discussionmentioning
confidence: 99%
“…Prior ex vivo studies have examined Raman spectral changes in explanted late stage OA cartilage tissues [20][21][22]33 or cartilage subjected to mechanical damage [16][17][18] . With the exception of Unal et al 33 , who used highwavenumber Raman peak ratios to measure cartilage water content but not GAG or collagen, prior Raman assessments have consisted of univariate peak analysis or principle component analysis (PCA), which do not provide quantification of biochemical or structural tissue changes relevant to the tissue's functional performance. Further, with the exception of Esmonde-White et al 19 , which used a probe to measure cartilage erosion, previous Raman investigations have been performed on benchtop microscopy systems that are incompatible with in situ intra-articular Raman evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Tong et al (2018) performed Raman spectral characterizations on porcine cartilage explants subjected to mechanical wear regimens, demonstrating a decrease in peak intensities corresponding to the protein backbone and amide bonds in collagen (817 and 1,670 cm −1 ). In an interesting novel analytical approach, Unal et al (2019) recently demonstrated that analysis of high wavenumber Raman spectroscopy (2,800 to 3,800 cm −1 ) can be used to detect the water fractions in articular cartilage (bound versus unbound water) and the elevated tissue swelling associated with OA - results that were correlated with MRI measurements. In an example of the implementation of fiber-optic Raman spectroscopy, Esmonde-White et al (2011) demonstrated that a fiber-optic probe can be used to assess cartilage thickness and mineralization degree in cadaver knee joint tissues.…”
Section: Raman Spectroscopy Of the Extracellular Matrixmentioning
confidence: 99%
“…[ 21 ] Finally, it has been shown that Raman bands at high wavenumbers (3,000–3,800 cm −1 ) are associated with water content, which has a significant correlation with the mechanical properties of human cartilage. [ 26 ]…”
Section: Introductionmentioning
confidence: 99%